Realizing the air brazing of ZrO2 ceramics through Al metal - Yaotian Yan (Journal of Materiomics, 2022)
The exploration towards cost-effective filler metal for ceramics joining has always been the key issues for ceramics joining. Herein, we reveal that the Al metal prefers to spread on the ZrO2 based ceramic under the air heating condition, due to the geometric limit effects by in-situ formed dense Al2O3 surface. Inspired by this, the joining of ZrO2 based ceramics was realized in air with Al metal as filler, through the diffusion of Al towards ceramic side. The Al element can induce obvious interfacial bonding effect on Al2O3 layer and ZrO2 ceramic, where the hybridization among the Al-p, Zr-d and O-p orbitals plays a key role. The in-situ formed Al2O3 layer on Al filler surface is vital for forming the fine interface (shear strength of ∼36 MPa), which results in the relief of lattice mismatch and peak stress at ceramic-filler metal transition interface.